Comparative Analysis of Traditional Methods with Activity Based Costing on Cost of Goods Produced by Yotta and Paduante Businesses - Nur abdi, Muhammad; Chairul Iksan Burhanuddin; Amran, Amran; Syamsuddin, Syamsuddin (International Journal of Economics, Business and Innovation Research, 2025)
MSMEs generally know the meaning of production costs, but do not understand the elements of calculating production costs, resulting in unreasonable determination of production costs. If MSMEs are unable to determine the cost of goods produced and the cost of goods sold accurately, it will have a negative impact on MSMEs in the long run. Quantitative Descriptive analysis method, with a case study research method regarding the comparative analysis of the Traditional method with the Activity Based Costing method on the calculation of Cost of Goods Manufactured at Yotta and Paduantea Businesses. The object used in this study is the Cost of Goods Manufactured using the Traditional method and the Activity Based Costing method. The unit of analysis used in this research is Yotta and Paduantea MSMEs. The results of calculations using the two methods result in differences in factory overhead charges which result in differences in the cost of goods produced. In the table above, Hazelnut Yotta is in a balanced condition where the difference figure is Rp. 0 and Green tea Paduan tea also experiences Overcosting or high costs of Rp. 14. Green tea Paduantea's COGS reported using the Traditional method is Rp.1,562 while the COGS with the Activity Based Costing method is Rp. 1,548, this shows that the reported COGS is Overcosting by Rp. 14, -. The COGS for Hazelnut Yotta reported using the Traditional method is Rp. 1,833 while the calculation of COGS with the Activity Based Costing method is Rp. 1,833.